Is the future magnetic? Magseed localisation for non palpable breast cancer. A multi-centre non randomised control study. Issue 11 (November 2019) - Zacharioudakis, Konstantinos; Down, Sue; Bholah, Zaheerah; Lee, Sum; Khan, Taherah; Maxwell, Anthony J.; Howe, Miles; Harvey, James
Abstract: Introduction: Magseed is an alternative method of localising non-palpable breast lesions that has addressed many of the limitations of wire guided localisation (WGL). It consists of a paramagnetic seed that can be visualised on mammography and ultrasound. Intraoperative localisation of the seed is achieved with the use of the Sentimag probe. The aim of this study was to prospectively compare localisation in patients undergoing wide local excision (WLE) for non-palpable lesions between Magseed and WGL. Methods: We prospectively collected data on all patients undergoing image-guided WLE between October 2017 and September 2018 in two academic breast units with a planned accrual of 100 consecutive patients undergoing Magseed localisation. Data was also collected on a cohort of 100 consecutive patients undergoing WGL in the same time period. Results: Demographic and disease characteristics were well balanced between the two groups. 4/104 patients were converted preoperatively from Magseed to WGL (2 misplaced Magseeds; 2 undetected Magseeds). Intraoperative identification and excision of the localised lesion was successful in all patients as confirmed with specimen radiography. Overall no significant differences were observed in the proportion of patients requiring re-excision between the two groups (Magseed 16% vs. WGL 14% p = 0.692). Specimens size by weight and volume was similar for both groups (Magseed 39.6 g vs. WGL 44.5 g p = 0.206 and 90.1 cm 3 for Magseed vs. 95.6 cm 3 for WGL p = 0.579). Conclusions: In our series Magseed localisation proved to be as reliable and effective as WGL in terms of lesion identification, excision with tumour free margins and specimen weight.